2004
DOI: 10.1159/000078768
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Interleukin-4 Production in Activated CD4+ T Cells by Diphthalate Plasticizers via Increased NF-AT Binding Activity

Abstract: Background: Diethylhexyl phthalate (DEHP) and diisononyl phthalate (DINP), two commonly used plasticizers in flexible polyvinylchloride formulations, have potentially adverse effects on human health. However, the influence of these diphthalates on allergic responses remains unclear. In this study we examined the effects of DEHP and DINP on IL-4 production in CD4+ T cells and the level of IgE in sera, critical hallmarks associated with allergic diseases. Methods: Mouse T cells were exposed to two diphthalates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 20 publications
2
50
0
Order By: Relevance
“…Treatment with BPA and NP, DEHP or DINP and HQ in vivo resulted in a significant increase of antigen-specific IgE levels in sera of antigenprimed mice (46,48,49). This supports the hypothesis that some EDs may have the ability to augment allergic processes.…”
Section: Influence On the Mammalian Organismsupporting
confidence: 74%
See 1 more Smart Citation
“…Treatment with BPA and NP, DEHP or DINP and HQ in vivo resulted in a significant increase of antigen-specific IgE levels in sera of antigenprimed mice (46,48,49). This supports the hypothesis that some EDs may have the ability to augment allergic processes.…”
Section: Influence On the Mammalian Organismsupporting
confidence: 74%
“…Treatment with DEHP or DINP in vivo resulted in a significant increase in IL-4 production in T cells. Furthermore, DEHP and DINP enhanced the activation of IL-4 gene promoter in T cells (48). Similar changes in cytokine synthesis induced by hydroquinone (HQ), a major metabolite of benzene present in large quantities in cigarette tar, were observed and there is some evidence that transcription factor NF-AT may be involved in this process (49).…”
Section: Influence On the Mammalian Organismmentioning
confidence: 80%
“…22,23 In addition, it can enhance serum immunoglobulin level and lung inflammatory cell levels in animals. 24 These observations point out that DEHP has the potential to interact with the immune system, thereby enhancing the development of allergic inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The route of exposure to phthalates is also of some interest. Subcutaneous or intraperitoneal injection of some phthalates such as DEHP has been shown to result in adjuvant effects on antibody responses to reference proteins at comparatively low doses (Larsen et al, 2001a(Larsen et al, ,b, 2002Lee et al, 2004). Both routes are favoured for experimental immunization (van Zijverden and Granum, 2000) and the former also for vaccination; however neither are routes by which individuals would commonly be exposed to phthalates in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that allergy and asthma result from a preferential activation of type 2 T cells [producing cytokines such as interleukin (IL)-4, IL-5 and IL-13] and the production of IgE antibody, the key biological mediator of the disease (Johannson, 2006;Sampson, 2004). Some investigators have reported that exposure to phthalates such as DEHP by nonphysiological routes (subcutaneous or intraperitoneal injection) resulted in enhanced antibody and/or cytokine responses stimulated by a reference protein (Larsen et al, 2001a(Larsen et al, ,b, 2002Lee et al, 2004). In contrast, we and others have demonstrated previously that topical exposure to DEHP, even under conditions where marked systemic effects were detected on liver weight, failed to cause adjuvant effects (Butala et al, 2004;Dearman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%